2016
DOI: 10.1182/blood-2015-11-682963
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors predictive of occult cancer detection in patients with unprovoked venous thromboembolism

Abstract: Key Points• It remains unclear whether a subgroup of high-risk patients could potentially benefit from a more extensive screening strategy.• Age, prior provoked VTE, and smoking status may be important predictors of occult cancer detection in patients with first unprovoked VTE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 12 publications
2
35
0
Order By: Relevance
“…40 Moreover, the associations between sP-selectin and both K s and CLT support growing evidence for the impact of platelet-derived proteins on clot properties reported previously. 41 We confirmed that older age 42 and higher platelet count 7 can predict cancer diagnosis following unprovoked VTE. We did not find male sex to be a risk factor, as opposed to the studies by Jara-Palomares et al 7 and Rieu et al, 43 although evidence for this issue is inconsistent.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…40 Moreover, the associations between sP-selectin and both K s and CLT support growing evidence for the impact of platelet-derived proteins on clot properties reported previously. 41 We confirmed that older age 42 and higher platelet count 7 can predict cancer diagnosis following unprovoked VTE. We did not find male sex to be a risk factor, as opposed to the studies by Jara-Palomares et al 7 and Rieu et al, 43 although evidence for this issue is inconsistent.…”
Section: Discussionsupporting
confidence: 61%
“…We did not find male sex to be a risk factor, as opposed to the studies by Jara-Palomares et al 7 and Rieu et al, 43 although evidence for this issue is inconsistent. 3,7,42 The associations between cancer and both diabetes and hypercholesterolemia likely result from older age of VTE patients diagnosed with malignancy (medians, 59 vs.…”
Section: Discussionmentioning
confidence: 99%
“…This has not previously been shown. Ihaddadene et al [17] found no association between sex and occult malignancy, Sørenssen et al [10] found no particular gender difference and Trujillo-Santos et al [15] found an odds ratio of 1.3 for male sex but did not reach significance. The explanation for the increased risk of a cancer diagnosis associated with male sex found here is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors predictive of occult cancer in patients with unprovoked VTE have already been identified. These include smoking, previous provoked VTE and older age (≥60 years) . Similarly, clinical prediction models incorporating multiple risk factors represent a promising approach for such risk stratification.…”
Section: The Futurementioning
confidence: 99%